Audit Keselamatan Jalan Sebagai Penanganan Kawasan Rawan Kecelakan Pada Ruas Trikora KM 2 - 4 Kota Banjarbaru Kalimantan Selatan: Road Safety Audit As A Measure For Handling Accident-Prone Areas On The Trikora Road Section KM 2–4, Banjarbaru City, South Kalimantan - Dyah Pradhitya Hardiani; Rizkan Maulidi Ansyari; Emma Ruhaidani (Media Ilmiah Teknik Sipil, 2026)
The Trikora Road section at Km 2–Km 4 in Banjarbaru City is one of the locations with a high rate of traffic accidents, making a road functional feasibility assessment necessary to evaluate road conditions and identify factors contributing to non-compliance with technical standards. This study aims to assess road functional feasibility based on the Regulation of the Minister of Public Works Number 11/PRT/M/2010 concerning Procedures and Requirements for Road Functional Feasibility. The research method was conducted through a field survey by comparing existing road conditions with technical standards for each road component and subcomponent, which were then classified into functional feasibility categories. The results indicate that 42.86% of the Trikora Road section falls into the Conditional Functional Feasibility (***) category, indicating that some technical requirements have been fulfilled and the road is still able to provide safety for road users. In addition, 42.86% of the section is categorized as Downgraded Functional Feasibility (**), indicating that several road components do not meet technical standards and require improvement. Meanwhile, the functional feasibility assessment of road facilities directly related to road users shows a Not Functionally Feasible (T) category of 14.29%, indicating the need for immediate corrective actions. The recommended improvements focus on enhancing road facilities and improving traffic management to reduce accident risk and increase road user safety and comfort.